KINERJA PERUSAHAAN: PENGARUH IT GOVERNANCE DAN KARAKTERISTIK DEWAN DI ERA REVOLUSI INDUSTRI 4.0 - Anita; Francesca, Cindy (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This research is conducted to analyze the effect of information technology (IT) governance and board characteristics on firm performance. This research uses IT governance, size of the board of directors, independent directors, proportion of female directors, remuneration of the board of directors, and foreign directors as independent variables with firm performance as measured by return on assets (ROA) and return on equity (ROE) as the dependent variable. This research uses a sample of 461 companies listed on the Indonesia Stock Exchange in 2016-2020 according to predetermined criteria. Panel data regression is used as a data analysis method in this research. This research shows that IT governance has a significant negative effect on firm performance (ROA), independent directors have a significant positive effect on firm performance (ROA), and foreign directors have a significant negative effect on company performance (ROE). However, size of the board of directors, proportion of female directors, and remuneration of the board of directors have no significant effect on firm performance (ROA and ROE).